Reinterpreting pluralism: A critical exegetical and intellectual analysis in contemporary Islamic thought - Rijal, Muhammad Syamsur; Hilmy, Muhammad Ihabuddin; Tanjung, Wahyudistira; Silfiani; Khaerussalam, Ahmad; Muhammad, Faiq Aqil; Fauziah, Amira; Lianti, Lia; Chilmiyah, Lu’lu’atil (Research Journal in Advanced Humanities, 2025)
In the face of intensifying currents of globalization and increasingly complex human interactions, the issue of pluralism has emerged as one of the most significant challenges in contemporary Islamic thought. This phenomenon is not confined to the theological realm but extends into social, cultural, and political dimensions that comprehensively impact the Muslim community. The diversity of interpretations of Qur'anic verses related to pluralism has given rise to a broad spectrum of understandings, reflecting both the intellectual richness and the complexity of the challenges faced by modern Muslims. This research aims to conduct an in-depth study of the concept of pluralism from the perspective of Qur'anic exegesis and the thought of contemporary Muslim scholars, with a focus on the discourse developing within the Indonesian context. By analyzing diverse interpretations, examining the views of proponents and critics, and exploring contextually relevant models of pluralism, this study seeks to build a strong theoretical foundation and offer practical contributions. The expected contributions include the development of a more dynamic and inclusive Islamic thought, the enhancement of interreligious harmony, and the provision of data-driven policy recommendations to assist stakeholders in supporting a pluralistic and just society.